2009
DOI: 10.1007/s10803-009-0726-3
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Effects of Pressure Vest Usage on Engagement and Problem Behaviors of a Young Child with Developmental Delays

Abstract: The purpose of this study was to examine the effects of wearing a pressure vest for a young boy with developmental delays. An A-B-A withdrawal design was used to examine the relation between wearing the pressure vest and child behaviors during a preschool art activity. Although the data showed moderate variability, no systematic differences were found in child engagement when the vest was worn and when the vest was not worn and problem behavior increased when the vest was being worn. These results are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…A recent review identified seven studies, four of which reported non-significant intervention results, leading to the reviewer conclusion that weighted vests are “ineffective” (Stephenson & Carter, 2009, p. 105). Three studies published after this review yielded similar negative and mixed findings for weighted vests (Hodgetts, Magill-Evans, & Misiaszek, 2011a, 2011b; Reichow, Barton, Good, & Wolery, 2009).…”
supporting
confidence: 56%
“…A recent review identified seven studies, four of which reported non-significant intervention results, leading to the reviewer conclusion that weighted vests are “ineffective” (Stephenson & Carter, 2009, p. 105). Three studies published after this review yielded similar negative and mixed findings for weighted vests (Hodgetts, Magill-Evans, & Misiaszek, 2011a, 2011b; Reichow, Barton, Good, & Wolery, 2009).…”
supporting
confidence: 56%
“…Although advocates of the therapies have cited positive effects in research, those studies have serious methodological flaws (Losinski et al, 2016). High-quality studies examining these constructs have consistently shown insignificant and, in some cases, negative effects as a result of DPT (e.g., Reichow, Barton, Good, & Wolery, 2009; Reichow, Barton, Sewell, Good, & Wolery, 2010). The results of this study corroborate the findings of Reichow and colleagues (Reichow et al, 2009; Reichow et al, 2010), in that we did not find the DPT interventions to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment effect in this study and in previous studies did not reach statistical significance, mainly because of the short intervention period. For example, Reichow et al reported a treatment period for a weighted vest lasting 20 school days,21 with intervention using the same method lasting for only 2 weeks in 2009 20. A longer intervention period could show a significant treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are limited to generalizations of clinical practice, while others focus on individual cases or other situations. Most of the earlier studies tested the use of a single sensory strategy, such as a weighted vest,12,14,15,20,21,24 ball chair,18 or seat cushion 6. Although these studies could discuss a single sensory strategy in depth, use of such a strategy is not sufficient to achieve the objective of educational plans at the individual level or to meet the needs of children in the classroom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation